Trade-off Analysis of Underwater Acoustic Sensor Networks - Tuna, G.; Das, R. (Iop Publishing Ltd, 2017)
In the last couple of decades, Underwater Acoustic Sensor Networks (UASNs) were started to be used for various commercial and non-commercial purposes. However, in underwater environments, there are some specific inherent constraints, such as high bit error rate, variable and large propagation delay, limited bandwidth capacity, and short-range communications, which severely degrade the performance of UASNs and limit the lifetime of underwater sensor nodes as well. Therefore, proving reliability of UASN applications poses a challenge. In this study, we try to balance energy consumption of underwater acoustic sensor networks and minimize end-to-end delay using an efficient node placement strategy. Our simulation results reveal that if the number of hops is reduced, energy consumption can be reduced. However, this increases end-to-end delay. Hence, application-specific requirements must be taken into consideration when determining a strategy for node deployment.
2nd International Conference on Automation, Control and Robotics Engineering (CACRE) -- JUN 28-30, 2017 -- Prague, CZECH REPUBLIC
Keywords: Energy-Delay Tradeoffs; Communication; Sound